IMPLEMENTATION OF ISLAMIC EDUCATION CURRICULUM IN CHILDREN WITH SPECIAL NEEDS IN EXCEPTIONAL SCHOOL API ALAM PAMEKASAN - Zainab, Nurul (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This article is a qualitative reseach result in SMPLB and SMALB Api Alam Pamekasan situated in Api Tak Kunjung Padam Street, Tlanakan district, Pamekasan. There are 14 students of SMPLB and 7 students of SMALB. The method used in this research is observation, deep interview and documentation. The primary source is taken from the deep interview with the PAI teacher and the headmaster of SLB Api Alam Pamekasan. The result of research show that the schools has not fully implemented 2013 curricula because they still use the KTSP book as their handbook. The implementation of PAI curricula runs well, it can be seen from the planning, implementation, assessment made by the teacher. The problems found in the implementation of PAI curriculum to students with special needs SLB Api Alam Pamekasan deals with the dynamic mood of the students and also the background of teachers’ education which is not Exceptional Education also need solution.